Digital Transformation of Land Administration: Strengthening Good Land Governance and Legal Certainty in Indonesia - Sisca Utami Damajanti (jfpublisher, 2026)
Land administration in Indonesia continues to face persistent problems, including overlapping ownership claims, land disputes, document forgery, and inconsistencies between physical and juridical data, conditions that underscore the importance of legal certainty in the governance of land rights. In response, the Government of Indonesia has pursued the digital transformation of land services, including electronic certificates and integrated land databases, as part of its broader bureaucratic reform agenda. This study aims to analyze how the digital transformation of land administration strengthens the application of Good Land Governance principles and enhances legal certainty over land rights, while identifying the challenges that continue to constrain its implementation. The study employs normative legal research using statutory, conceptual, and analytical approaches, examining primary legal materials, including the 1945 Constitution, the Basic Agrarian Law, Government Regulation Number 18 of 2021, and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1 of 2021, alongside secondary legal literature. The findings show that digital transformation strengthens transparency, accountability, effectiveness, efficiency, and legal certainty in land administration, while reducing opportunities for maladministration and document fraud. However, its success remains constrained by uneven technological infrastructure, cybersecurity risks, personal-data-protection requirements, limited inter-agency interoperability, and uneven human-resource readiness, all of which require continued regulatory and institutional strengthening.